Returns co-movement and interconnectedness: Evidence from Indonesia banking system - Zuhrohtun Zuhrohtun; M. Zulkifli Salim; Kunti Sunaryo; Sri Astuti (Cogent Economics & Finance, 2023)
In this paper, we explore how asset returns used as a proxy to detect interconnectedness of systemic risk in the financial system. Our sample employs a mixture of Indonesian banks' public and prudential data over the 2012-2019 period. Using the Principal Component Analysis and Granger causality the core banks in the network could explain the variance, risk co-movement, and show shocks propagation. Further, the results are also in line with Basel indicator-based to score the interconnectedness. The dominance of big size banks in the centrality measures raises issue of substitutability. This paper outstretched theories and their application provides a basis for policy makers to develop supervision frameworks to mitigate systemic risk.
Keywords: G21; G210; G28; G280; 330; Granger causality; interconnectedness; principal component analysis; systemic Risk